2018
DOI: 10.14687/jhs.v15i2.5162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of leader-member exchange on job performance of academic staff: An empirical evidence from higher education institutions

Abstract: Recently, the relationship between leader-member exchange and job performance has become more interesting subject among researchers. However, the literature has a paucity of empirical studies conducted in the higher education institutions; therefore, the relationship between these two variables is not clear. Hence, the purpose of this study was to examine the effect of leader-member exchange on the job performance of academic staff in higher educational institutions. The data for the study were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
4
0
2
Order By: Relevance
“…These results indicate that the quality of the LMX relationship with the employees is important in order to achieve the desired results in terms of business. The results obtained in this study are supported by many studies in the literature, indicating that the quality of the LMX relationship, which is characterized by a high level of trust, commitment, and loyalty, that the leader will establish with his subordinates, affects the job performance of the subordinates positively (Özutku et al, 2008;Loi et al, 2011;Akkoç, 2012;Turgut et al, 2015;Karayel et al, 2018;Tekin, 2018;Duyan and Yıldız, 2018;Akman, 2021;Biçer, 2021). The conscious increase of the support received from the leader is reflected as a positive effect on the job performance of the employee.…”
Section: Conclusion and Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results indicate that the quality of the LMX relationship with the employees is important in order to achieve the desired results in terms of business. The results obtained in this study are supported by many studies in the literature, indicating that the quality of the LMX relationship, which is characterized by a high level of trust, commitment, and loyalty, that the leader will establish with his subordinates, affects the job performance of the subordinates positively (Özutku et al, 2008;Loi et al, 2011;Akkoç, 2012;Turgut et al, 2015;Karayel et al, 2018;Tekin, 2018;Duyan and Yıldız, 2018;Akman, 2021;Biçer, 2021). The conscious increase of the support received from the leader is reflected as a positive effect on the job performance of the employee.…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…In regards to several benefits which were taken from managers, employees can be willing to provide high performance and make contributions beyond far more than the formal employment contract (Howell and Hall-Merenda, 1999: 682;Cerit, 2012: 36;Çalışkan, 2018: 109). Relevant literature also supports that high-quality LMX relationships have a positive effect on job performance (Özutku et al, 2008;Loi et al, 2011;Akkoç, 2012;Turgut et al, 2015;Karayel et al, 2018;Tekin, 2018;Duyan and Yıldız, 2018;Akman, 2021;Biçer, 2021).…”
Section: Leader-member Exchangementioning
confidence: 96%
See 1 more Smart Citation
“…Shaikh et al (2019) found that leader-member exchange had a positive and significant effect on job satisfaction in a study they conducted on bank employees. Duyan and Yildiz (2018) determined that leader-member exchange affects job performance positively in their research on faculty members working in faculties of sports sciences. Moreover, other studies in the literature concluded that the leader-member exchange of the employees positively affects job satisfaction (Aslan, 2019;Eşitti & Kasap, 2020;Pan et al, 2021).…”
Section: Display Of Analysis Results On Modelmentioning
confidence: 99%
“…El liderazgo transformacional se basa en las dimensiones de consideración individual, estimulación intelectual, motivación inspiracional e influencia idealizada atribuida, influencia idealizada conductual [25,29]. De esta manera, los equipos de estudiantes altos en liderazgo transformacional se componen por individuos donde se favorece el entusiasmo y un cuidado entre estos [29], fomentando la creatividad en el desarrollo de las tareas [34], estos procesos ayudarían a que los estudiantes se puedan alinear con los objetivos, pudiendo autorregularse y autodirigirse de una manera más eficiente [25,35]. Estas características positivas desarrollarían un ambiente propicio para que el proceso de liderazgo surja en los estudiantes y se distribuya en el equipo, ya que por un lado se sentirían en un espacio agradable de trabajo y por el otro lado sentirían una motivación para liderar y además un apoyo constante para el desarrollo de las tareas.…”
Section: Hipótesis Del Estudiounclassified